Gender and preterm birth: Is male fetal gender a clinically important risk factor for preterm birth in high-risk women? - Teoh, P.J.; Ridout, A.; Seed, P.; Tribe, R.M.; Shennan, A.H. (European journal of obstetrics & gynecology and reproductive biology, 2018)
Gender differences in several adverse pregnancy outcomes have been described, including preterm labour and delivery. In the low risk population, the male fetus is at significantly higher risk of spontaneous preterm birth. Our objective was to examine the risk effect of fetal gender on pregnant women at higher risk of preterm birth, and therefore its potential impact on targeting management. This was an analysis of prospectively collected data from a dedicated inner-city Prematurity Surveillance Clinic over a sixteen-year period. All women were high-risk for preterm delivery in view of their history, which included previous late miscarriage, PTB or significant cervical surgery. Obstetric variables and pregnancy outcomes were compared in male and female babies. Demographic and risk factors were compared between groups, and both spontaneous and iatrogenic preterm delivery rates interrogated (<24, <28, <34 and <37 weeks’ gestation). Risk ratios (with 95% confidence intervals) were calculated for each gestational band. In this cohort, 14.5% of women (363/2505) delivered before 37 weeks. Pregnant women were stratified by fetal gender and were comparable for referral risk factors and demographic characteristics. There was no significant association between fetal gender and incidence of miscarriage less than 24 weeks (RR 1.17, 95% CI 0.65–2.10, p = 0.607), or preterm births 24 to 37 weeks RR 1.07 (95% CI 0.82–1.40, p = 0.383). Furthermore, analysis by gestational band [<28 RR 0.91 (95% CI 0.60–1.37, p = 0.647), <34 RR 1.18 (95% CI 0.89–1.57, p = 0.257 and <37 weeks RR 1.10 (95% CI 0.91–1.33, p = 0.309)] also showed no effect. This held true for both spontaneous and iatrogenic preterm delivery. In our high-risk cohort there was no gender difference for preeclampsia (RR 0.93, 95% CI 0.61 to 1.41, p = 0.725) or preterm premature rupture of membranes (PPROM) (RR 1.14, 95% CI 0.86 to 1.50, p = 0.384) In a high-risk cohort there was no significant increased risk of miscarriage, spontaneous or iatrogenic PTB, preeclampsia or PPROM for the male fetus. This is contradictory to low-risk populations and confirms that gender need not be integrated into high-risk management protocols for preterm birth.